Blood pressure and all-cause mortality in dementia: a nationwide cohort study. - Yoo, Jung Eun; Han, Kyungdo; Jung, Jin-Hyung; Park, Kye-Yeung; Lee, Chung-Woo; Shin, Dong Wook; Nam, Ga Eun (Age & Ageing, 2025)
Background Comorbidities are crucial in managing hypertension, but studies on individuals with dementia are lack. This study investigated the association between blood pressure (BP) and all-cause mortality in dementia. Methods We analysed 146 832 individuals newly diagnosed with dementia (2008–2016) who underwent national health screening within 4 years after their dementia diagnosis. Dementia was defined using prescriptions for anti-dementia medications and relevant ICD-10 codes. Participants were categorised by systolic BP (SBP) and diastolic BP (DBP). All-cause mortality was assessed using multivariable Cox proportional hazards regression. Results The cohort's mean age was 75.1 years, with 35.5% men. Over a mean follow-up of 3.7 years, there were 52,118 deaths (35.5%). A reverse J-shaped association was observed between SBP and mortality, with nadir at SBP 138 mmHg on cubic spline curve (P for trend <.001). Compared to SBP 120–129 mmHg, mortality increased for SBP <100 mmHg [adjusted hazard ratio (aHR) 1.17, 95% confidence interval (CI) 1.11–1.24] and SBP ≥160 mmHg (aHR 1.08, 95% CI 1.04–1.13). Mortality increased linearly with higher DBP (P for trend.001), with DBP ≥90 mmHg associated with higher risk (aHR 1.10, 95% CI 1.05–1.16 for DBP ≥100 mmHg) relative to DBP 70–79 mmHg. These associations were maintained in dementia subtypes and after stratification, with a greater strength observed for older people and antihypertensive drugs use. Conclusions Individuals with dementia were revealed to have a reverse J-shaped association between SBP and all-cause mortality. The risk significantly increased with higher DBP, starting from ≥90 mmHg.